Characterization of CYCLOIDEA-like genes in Proteaceae, a basal eudicot family with multiple shifts in floral symmetry. (26th December 2016) - Citerne, Hélène L.; Reyes, Elisabeth; Le Guilloux, Martine; Delannoy, Etienne; Simonnet, Franck; Sauquet, Hervé; Weston, Peter H.; Nadot, Sophie; Damerval, Catherine
Abstract : Background and Aims The basal eudicot family Proteaceae (approx. 1700 species) shows considerable variation in floral symmetry but has received little attention in studies of evolutionary development at the genetic level. A framework for understanding the shifts in floral symmetry in Proteaceae is provided by reconstructing ancestral states on an upated phylogeny of the family, and homologues of CYCLOIDEA ( CYC ), a key gene for the control of floral symmetry in both monocots and eudicots, are characterized. Methods Perianth symmetry transitions were reconstructed on a new species-level tree using parsimony and maximum likelihood. CYC -like genes in 35 species (31 genera) of Proteaceae were sequenced and their phylogeny was reconstructed. Shifts in selection pressure following gene duplication were investigated using nested branch-site models of sequence evolution. Expression patterns of CYC homologues were characterized in three species of Grevillea with different types of floral symmetry. Key Results Zygomorphy has evolved 10–18 times independently in Proteaceae from actinomorphic ancestors, with at least four reversals to actinomorphy. A single duplication of CYC -like genes occurred prior to the diversification of Proteaceae, with putative loss or divergence of the ProtCYC1 paralogue in more than half of the species sampled. No shifts in selection pressure were detected in the branches subtending the two ProtCYC paralogues. However, the amino acid sequence preceding the TCP domain is strongly divergent in Grevillea ProtCYC1 compared with other species . ProtCYC genes were expressed in developing flowers of both actinomorphic and zygomorphic Grevillea species, with late asymmetric expression in the perianth of the latter. Conclusion Proteaceae is a remarkable family in terms of the number of transitions in floral symmetry. Furthermore, although CYC -like genes in Grevillea have unusual sequence characteristics, they display patterns of expression that make them good candidates for playing a role in the establishment of floral symmetry.